Diálogos entre processos formativos e a prática em enfermagem - Cavalcante, Rosangela Diniz (2019)
Research with the objective of evaluating, together with the graduates, the articulation between training processes and professional practice, through the National Curriculum and Content Standards for Nursing undergraduate courses in the state of Rio Grande do Norte. This is an exploratory, transversal, descriptive and inferential study of quali-quantitative approach. Registered nurses from eight Higher Education Institutions (HEIs) enrolled in the Nursing Regional Council of the state in the corresponding period from 2014 to 2016. The sample was probabilistic and stratified with proportional allocation by HEI. Data were collected between August 2017 and March 2018. Quantitative data were collected through the application of structured questionnaires. From these, 174 were used in the analysis of descriptive and inferential statistics. Qualitative data were obtained in 15 semi-structured interviews and submitted to the content analysis technique in the lexical mode. In the quantitative analysis, a statistical association was identified between the legal nature of the HEI and six variables of characterization after the chi-square test. Regarding the training according to the guidelines of the National Curriculum, the graduates evaluated negatively: the student participation in the construction of the pedagogical project of the course, the preparation in the administration of conflicts in the health team; the training of other health professionals; the use of data and tools in professional research and the articulation between teaching, research and extension activities. The items that were better evaluated were: the ethical and humanistic dimension; the development of promotion activities, prevention and rehabilitation actions according to individual and collective needs; the diversity of scenarios of practices and stages and the assistance dimension in the different life cycles. After performing the Mann-Whitney test between the items of the dimensions evaluated and the legal nature of HEI, statistically significant differences were found in 4 items: articulation between teaching, research and extension; opportunities for tutoring, extension and scientific initiation activities; knowledge about the social structure and its influence for the organization of nursing and articulation of the pedagogical project of the course with the Nursing National Curriculum. Thus, it is possible to affirm that, in relation to these aspects, the training in public HEIs was better evaluated compared to the training offered by private HEIs. In the qualitative analysis, the interviews were transformed into a single textual corpus and submitted to the treatment of the Descending Hierarchical Classification (DHC), obtaining retention of 84,20%. The DHC resulted in two analytical categories, the first subdivided into three classes (1, 4 and 5) and the second into two classes (2 and 3). Classes 1, 4 and 5 addressed the challenges of nursing training in the job market. In class 1, among the fragilities presented there are: hospital clinical training, the leadership/management approach, and health planning. Class 4 addressed didactic-pedagogical issues such as: the role of the teacher/mediator in the construction of knowledge, the organization of disciplines and workload and the quality of the infrastructure of laboratories and libraries offered by HEIs. The theme of class 5 was the importance of training in the reality of health services, separating the historical dichotomy between theory and practice as it progresses in the articulation between teaching/service and community. Classes 2 and 3 discuss the role of training institutions in the reorientation and strengthening of nursing education. To this end, graduates suggest improving the stimulation of the scientific and political dimension in training, as a trigger for significant changes in the nursing profession and, consequently, in their professional practice. They also suggest an increase in the supply of non-compulsory curricular activities such as: tutoring, extension activities, non-compulsory internships and research. In addition, they point out the need to expand partnerships, especially with the private initiative, as well as the incentive to entrepreneurship and the search for cooperation and participation in the teaching of entities representing this working class. Therefore, evaluating the elements of nursing education is necessary, considering that it will reflect about the insertion of nurses in the health job market. Therefore, training should not be in the service of marketing needs; however, a dialogue must be in place, so that higher education can contribute to the formation of professionals with an ethical/political profile capable of exercising their citizenship rights in the search for assured rights and working conditions for the development of their productive functions.